Developing a personalized heterologous prime boost vaccination strategy for tumor therapy - Ramirez-Valdez, RA (2021)
The limited success of therapeutic cancer vaccines to date is likely due to sub-optimal generation of anti-tumor CD8 T cells and insufficient tumor microenvironment (TME) modulation. In this study, a novel intravenous (IV) heterologous prime-boost vaccination strategy with a self-assembling neoantigen-peptide nanoparticle TLR-7/8 agonist (SNP) vaccine platform and a chimp adenovirus (ChAdOx1) was used to elicit high magnitude neoantigen-specific CD8 T cells and modulate the TME. Mice primed with SNP encoding the neoantigen Reps1 for a colon carcinoma (MC38) and boosted with ChAdOx1 IV encoding Reps1 elicited on average ~40% Reps1-specific CD8 T cell responses, which were ~4x higher than mice boosted by the conventional IM route. These CD8 T cells were capable of mediating protection from tumor challenge in a prophylactic setting experiment. Therapeutically, heterologous prime-boost with ChAdOx1 given IV or IM enhanced protection compared to the use of ChAdOx1 alone. Remarkably, IV administration of ‘empty’ ChAdOx1 (not encoding Reps1) after Reps1-SNP prime also improved protection compared to Reps1-SNP prime or ChAdOx1 prime alone. Subsequently, IV vaccination with ChAdOx1 or SNP was found to induce production of IFNα and activation of cDC1s in the spleen, tumor and tumor-draining lymph node (td-LN). The activation of cDC1s was found to be dependent on functional IFNα signaling and blockade of IFNα signaling at the time of boost completely abrogated tumor regression in the therapeutic setting. Together, these data suggest that IV ChAdOx1 boosting not only increases the magnitude of antigen-specific CD8 T cells, but also modulates the TME to promote tumor regression, representing a readily translatable therapeutic paradigm to drive the Cancer Immunity Cycle.